Assessing the Endogeneity of OCA Conditions in EMU - Vieira, Carlos (2012)
The academic and political discussion about which countries met the conditions for joining EMU was decisively influenced by the Frankel and Rose (1997) hypothesis concerning endogenous OCA properties. The answer to their question "Is EMU more justifiable ex post than ex ante?" was a definite yes in their ex ante analysis. Our ex post examination of the euro's first decade suggests however that the hypothesis does not hold for some countries. This paper utilizes panel data estimation techniques to compute OCA indices that help assess the OCA endogeneity hypothesis and signal current external and fiscal imbalances.